Future of Us - Asher, Jay; Mackler, Carolyn (New York : Razorbill, 2011)
It's 1996, and less than half of all American high school students have ever used the Internet. Emma just got her first computer and Josh is her best friend. They power up and log on--and discover themselves on Facebook, fifteen years in the future. Everybody wonders what their Destiny will be. Josh and Emma are about to find out.
690L
Keywords: High schools; Friendship; Internet; Young adult fiction